A New Routing Protocol with High Energy Efficiency and Reliability for Data Delivery in Mobile Ad Hoc Networks - Mahfuzur Rahman Bosunia; Daniel P. Jeong; Chanhong Park; Seong-Ho Jeong (International Journal of Distributed Sensor Networks)
The proliferation of mobile devices has changed the trends by which people access and share contents in the communication world, leading to migration from the wired to wireless networks with high expectations of ubiquitous connectivity. These trends have motivated researchers to have interests in the future advanced mobile communications. In this paper, we concentrate on one of the most promising types of network, that is, mobile ad hoc network (MANET). Due to the highly dynamic network topology and resource shortage of MANET and the limited energy of communicating nodes, the communication route among nodes may fail frequently. To increase the applicability and sustainability of MANET in the future communication environment, we propose here a new routing protocol that constructs a stable, a reliable, and the shortest route having nodes with the minimum level of remaining energy to increase the operational lifetime of MANET. It also introduces a recovery scheme that reduces the network control overhead significantly to increase the reliability of the network. The effectiveness and robustness of our protocol and the corresponding data delivery mechanism make an ideal solution that can go a long way toward effective data dissemination in the future network.